Analysis Of Marketing Strategies At F2r Dira In Manna South Bengkulu District - Nur Mohammad Syahputra; Tito Irwanto; Yudi Irawan Abi; Yun Fitriano (UNIVED Press, 2024)
The aim of the research is to analyze the marketing strategy at F2R Dira in Manna, South Bengkulu Regency. The sample in this study was 55 people, namely 5 employees at F2R Manna, South Bengkulu Regency and 50 customers. The analysis method used is SWOT analysis which consists of an Internal Strategy Factor Matrix (IFAS) and an External Strategy Factor Matrix (EFAS). The result of adding up the strengths is 22.00 while the weaknesses are 11.34, so the internal factor quadrant is 22.00 – 11.34= 10.66, meaning the ability of F2R Dira in Manna, South Bengkulu Regency to utilize strengths and minimize weaknesses. is internal. The opportunity for this strategy is 19.90 and the threat is 11.59. So the external factor quadrant is 19.90 – 11.59 = 8.31, meaning the high ability of F2R Dira in Manna, South Bengkulu Regency in exploiting opportunities and overcoming threats faced by F2R Dira. Dira's F2R strategy in Manna, South Bengkulu Regency supports an aggressive strategy, or SO strategy in the SWOT matrix, namely producing contemporary souvenirs, promoting products through social media and expanding product market areas by selling online.